THE CHALLENGES OF USING SOCIAL MEDIA APPLICATIONS IN LEARNING ENGLISH AS A FOREIGN LANGUAGE AT BUSINESS ENGLISH COMMUNICATION PROGRAM - Andini, Andi Nurul; Patak, Andi Anto; Amin, Fatimah Hidayahni (JTechLP: Journal of Technology in Language Pedagogy, 2023)
This study aims to identify and explain the challenges Business English communication programs face when learning English through social media Instagram, TikTok, YouTube and Twitter. Qualitative methods are used in this study. This study uses interview questions to collect data, the participants of this study are seven students from the business English communication program. Based on research findings, it can be concluded that there are many challenges that cause difficulties when students use social media to learn English. This is a tool that students use to monitor boredom, social media, and mixed video and social media.